ILMU PENGETAHUAN SOSIAL DENGAN HADIS NABISOCIAL SCIENCE WITH PROPHETIC HADITH - Bayu Bayu (CV. ADIBA AISHA AMIRA, 2024)
Explanation of Islamic views regarding these social problems is very necessary, so that every Muslim is aware of what they should do and what they should abandon. Because apart from regulating human beliefs, Islam also regulates their lives. The purpose of this writing is an effort to integrate hadith with social science. The object of sociological study is society and human social behavior by examining groups. This group includes researching families, ethnic or ethnic groups, government communities and various social, religious, political, cultural and other organizations. Social science and hadith science are two separate sciences but have the same dimension, namely human. These two sciences can be integrated as a blend. The scope of social science can be grouped into several disciplines which are categorized as social science, namely sociology, anthropology, geography, economics, history, psychology, law and political science.